DHIKIR DALAM AL -QUR’AN: Kajian Fadilah Dhikir Menurut Mufasir Kontemporer - Syaifudin, Syaifudin (SAMAWAT: Journal Of Hadith and Qur'anic Studies, 2021)
One of the words that is often mentioned in the Qur'an is dhikr which is also a suggestion or a means for believers to be able to purify their hearts and draw closer to Allah SWT. and the need for Allah through amaliah which is always associated with the various worships in Islam.One of the methodologies in interpreting the Qur'an is the interpretation with the maud{u>iy approach, besides that the author also directs or classifies in his discussion by taking contemporary interpretations, namely starting from the 20th century, among the interpretations that will be used by the author are the interpretation of Al-Mishbah by M. Quraish Shihab and the interpretation of Al-Azhar by Abdul Malik Abdul Karim Amrullah (Hamka) and Hasbi Ash Shiddieqy.From this, it is hoped that it can help and facilitate the author in carrying out research and provide a development in the treasures of Islamic science that can be used as a reference in scientific contributions so that the hope of the author is that in the end, the study of dhikr in the Qur'an is the study of fadlah dhikr according to commentators. Contemporary thought can give the nuances of thinking characteristically Islamic.Keywords: dhikr, contemporary interpretation